An analysis of slang words in Mean Girls (2024) movie - Tifanny Maulidya Hanafi; Ririn Setyowati (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This research aims to identify the types of slang words used by the characters in Mean Girls (2024) and analyse their functions through social dimensions. This research applied a qualitative approach, with data collected from the dialogues of the four main characters: Regina, Cady, Gretchen and Karen, focusing on slang expression found in their conversations. The slang words were classified based on Allan and Burridge’s (2006) theory, which includes Fresh and Creative, Flippant, Imitative, Acronym, and Clipping. Additionally, Holmes’ (2013) social dimension theory was used to explore how slang functioned in different social contexts, particularly in terms of solidarity, status, formality, and functional meaning. From the analysis, the findings showed that all five slang types appeared in the film, each serving different purposes depending on the situation. Some slang words were used to establish group identity and reinforce friendships, while others helped characters reinforce dominance or add humor. Moreover, the use of slang was not only a reflection of informal speech but also a means of strengthening friendships, gaining control, and maintaining social identity.